THE IMPORTANCE OF THE TIME FACTOR IN THE ANALYSIS OF ECONOMIC PROCESSES - Agabekov Absattar Yuldashevich (Scholar Express Journals, 2025)
The article summarizes economists scientists opinions about the role of the time factor in economy/ The author cons the time factor not only as a source of economy but alsoras one of the main elements of the usefulness of capital and consumer goods.
Keywords: Economic Time; Resource; Cost